Islamic education management paradigm and dynamics of contemporary education in the era of kurikulum merdeka - R A Mustika Hariyanti; Agus Apriansyah; Zaiyad Namiri; Agus Pahrudin (12 Waiheru, 2024)
The research aims to analyze the management paradigm of Islamic education and the dynamics of contemporary education in the era of the kurikulum merdeka so that it can transform and have attitudes and behavior that can compete, be creative, and innovative while still referring to Islamic education. The research method uses qualitative research, with the type of research being a case study. Data was obtained through surveys and observations, which were then described naturally by researchers. Data analysis was carried out using inductive data analysis. Data analysis was carried out through 3 stages: data reduction, data presentation, and data conclusion. Research findings show that Islamic schools embody a new paradigm for successful Islamic education management. With merdeka belajar, learning is accessible and unbound, which moves students to develop their full potential to achieve intellectual, moral, and other skills. Independence is given to students with direction and guidance from the teacher. Freedom to learn from an Islamic perspective is an internal process that moves students to use all their natural, cognitive, affective, and psychomotor potential independently to become human beings who have various intellectual capabilities, skills, and morals, carrying out the mission of rahmatan lil a'lamin to worship Allah SWT.